Leonardo da Vinci - Isaacson, Walter (Simon & Schuster, 2017)
"He was history's most creative genius. What secrets can he teach us? The author of the acclaimed bestsellers Steve Jobs, Einstein, and Benjamin Franklin brings Leonardo da Vinci to life in this exciting new biography. Based on thousands of pages from Leonardo's astonishing notebooks and new discoveries about his life and work, Walter Isaacson weaves a narrative that connects his art to his science. He shows how Leonardo's genius was based on skills we can improve in ourselves, such as passionate curiosity, careful observation, and an imagination so playful that it flirted with fantasy. He produced the two most famous paintings in history, The Last Supper and the Mona Lisa. But in his own mind, he was just as much a man of science and technology. With a passion that sometimes became obsessive, he pursued innovative studies of anatomy, fossils, birds, the heart, flying machines, botany, geology, and weaponry. His ability to stand at the crossroads of the humanities and the sciences, made iconic by his drawing of Vitruvian Man, made him history's most creative genius"--